A novel UV-curable extravascular stent to prevent restenosis of venous grafts. (15th November 2021) - Dai, Chun; Chu, Tianshu; Li, Xiang; Jiang, Hui; Liu, Tan; Zhou, Yang; Gao, Lei; Shen, Cheng; Ge, Jianjun
Abstract: The incidence of coronary heart disease is increasing yearly. Coronary artery bypass graft (CABG) is an important surgical method for the treatment of coronary heart disease. The vein grafts in CABG surgery mostly use saphenous vein, but restenosis of the graft frequently occurs, and has become an urgent clinical problem. In this study, we produced a UV-curable Hydroxyethyl Methacrylate (HEMA) gel containing Bletilla striata, and compared its tensile strength and expansibility to that of human vessels, showing that the film has good physical properties. Through cell experiments, we proved that film has no effect on cell proliferation, migration, apoptosis, and DNA damage. In addition, we placed the film under the skin of mice to measure inflammation-related cells and factors, and found that it did not trigger the body's immune response. After that, we designed a rat vein graft model to simulate the pathological changes of the vein graft vessel after CABG. The film had a good inhibitory effect on the restenosis of vein graft vessels in the rat model. Finally, analysis of the expression levels of proteins involved in the proliferation and migration indicated that the gel can effectively inhibit these processes in smooth muscle cells in the graft vein. In conclusion, this study has successfully produced a UV-curable HEMA gel containing B. striata that could effectively inhibit the restenosis of vein grafts. Graphical abstract: Fig Abstract: a: In CABG, the saphenous vein is removed and grafted onto the coronary arteries of the heart. b：The gelatinous scaffold is wrapped around the vessel while in liquid state. After UV curing, the scaffold can provide support for the vein graft. Image 1 Highlights: The extravascular stents can be cured under UV light. The extravascular stent can encapsulate Bletilla striata polysaccharide and release it stably. The extravascular stents can effectively inhibit vascular restenosis. The extravascular stent has good histocompatibility and cytocompatibility.